Multiple faces of the same pathology - Ng, KS; Fazarina M,; Anizah Ali,; Shuhaila A,; Yulianty Arifuddin,; Zainul Rashid Mohd. Razi, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Ectopic pregnancy is defined as an extrauterine pregnancy. We report three cases where the ectopic pregnancies were implanted in different sites. The first case was a 28-year-old in her second pregnancy at 9 weeks gestation. She presented with painless vaginal bleeding. Ultrasound showed unruptured cornual pregnancy with hCG level of 7456mIU/ml. A single dose of 75mg IM methorexate was given and she responded well with significant reduction of hCG level. The second case, a 26-year-old gravida 5 para 2+2, with 2 previous ectopic pregnancies and bilateral salpingectomy, conceived via in-vitro fertilization (IVF). She presented with acute abdomen and one episode of syncope at 8 weeks 4 days gestation. Laparotomy showed ruptured ectopic pregnancy at the left tubal stump requiring a left salpingectomy. The third case was a 26-year-old, gravida 5 para 2+2, with two previous vaginal deliveries and two previous first trimester miscarriages. Her menses was irregular since she took injectable progestin. She presented to the emergency department with sudden onset of lower abdomen pain. Urine pregnancy test was positive. Ultrasound showed empty uterus, no adnexal mass but there was significant free fluid in the cul-de-sac. During laparoscopy, a ruptured ovarian pregnancy was diagnosed and salpingo-oophorectomy performed. There was no significant risk factor contributing to ectopic pregnancy identified in the first and third case. In the second case, despite previous bilateral salpingectomy, the patient still had ectopic pregnancy in the left fallopian tube remnant.